Additively Manufactured Ferroelectric Particulate Composites for Antimicrobial Applications. Issue 7 (11th March 2023) - Tsikriteas, Zois Michail; Heylen, Rachel A.; Jindal, Swati; Mancuso, Elena; Li, Zihe; Khanbareh, Hamideh
Abstract: A polarized ferroelectric material can initiate the micro‐electrolysis of water molecules which leads to the formation of reactive oxygen species (ROS) in an aqueous solution resulting in selective bacteria killing. This study presents the fabrication, characterization, and antimicrobial performance of poled ferroelectric particulate composites. Barium calcium zirconate titanate (BCZT) micro‐powder is synthesized by a solid‐state reaction and mechanically mixed with polycaprolactone (PCL) to be subsequently fed into the 3D bioprinter for the fabrication of porous PCL‐BCZT structures at four different ceramic loadings (0, 10, 20, 30 wt%). For the examination of material's capacity to handle extremely high contamination, the composites are exposed to a high inoculum of bacteria ( Escherichia coli ATCC 25922) ≈70% of E. coli degradation is recorded at the end of 15 min without any external intervention. The surface selective bacterial degradation can be attributed to the generated reactive oxygen species, the large surface area of the porous samples and polymer matrix's hydrophobic nature, behavior which can be reflected in the composites with 30 wt% of BCZT loading exhibiting the best antimicrobial performance among the other state‐of‐the‐art ferroelectrics. Overall, these results indicate that the poled composites have a great potential as antimicrobial materials and surfaces. Abstract : The study examines the fabrication, characterization, and antimicrobial performance of ferroelectric composites composed of barium calcium zirconate titanate and polycaprolactone. Results show that the composites have a great potential as antimicrobial materials with 70% degradation of E. coli bacteria recorded after 15 min without external intervention. The highest filler loaded composite show the best performance among the state‐of‐the‐art antimicrobial ferroelectric.